HANNAH ARENDT’S “POLITICAL BEINGS” AS A REPRESENTATION OF POLITICAL EXISTENTIALISM FOR HUMANS EXISTING IN THE WORLD - Lustanto, Rendi; Kartika, Ganang Dwi (UI Scholars Hub, 2019)
Discussions in politics often focus on a broad range of political systems or political movements. This focus leads to the efforts to direct the public to the conversation of